Odpowiedź :
Odpowiedź:
[tex]\begin{itemize}\\\Large\\\left \{ {{x=\frac{3}{2} } \atop {y=-\frac{1}{3} }} \right.[/tex]
Szczegółowe wyjaśnienie:
[tex]\begin{itemize}\\\\\Large\\\left \{ {{4x-3y=7} \atop {-8x+9y=-15}} \right. }\\\\[/tex]
Pierwsze równanie mnożymy obustronnie przez 2
[tex]\begin{itemize}\\\Large\\\left \{ {{8x-6y=14} \atop {-8x+9y=-15}} \right.[/tex]
Dodajemy stronami
[tex]3y=-1\\\\y=-\frac{1}{3} \\\\x=\frac{7+3y}{4} =\frac{7-1}{4} =\frac{3}{2}[/tex]
Czyli:
[tex]\begin{itemize}\\\Large\\\left \{ {{x=\frac{3}{2} } \atop {y=-\frac{1}{3} }} \right.[/tex]